Does CEO popularity affect climate change disclosure? Evidence from Indonesian firms - Chandra, Budi; Ramadana, Mariska; Robin, Robin; Melysa, Melysa; Surny, Surny (Jurnal Siasat Bisnis, 2026)
Purpose – This study examines the effect of CEO popularity, including celebrity CEO (CELEB) and star CEO (STAR) on climate change disclosure (CCD) in Indonesian firms.Design/methodology/approach – This study analyzes data from 2020 to 2023, sourced from companies listed on the Indonesia Stock Exchange (IDX), and applies several statistical methods, including data panel regression to examine the relationship between CELEB and STAR to CCD, coarsened exact matching (CEM) to reduce selection bias, generalized least squares (GLS) to address heteroskedasticity and autocorrelation, and the two-stage Heckman model to mitigate endogeneity arising from sample selection bias. We further conducted a comparative analysis between firms led by STAR and NON-STAR to investigate whether the impact of CEO characteristics differs across the two groups.Findings – The empirical results show that both measures of CEO popularity are positively and significantly associated with the level of CCD. Firms led by CELEB or STAR consistently exhibit higher CCD scores compared firms led by less prominent executives. This finding indicates that CEO popularity is a meaningful explanatory factor in explaining cross-sectional variation in CCD.Research limitations/implications – This study is limited by proxy-based measures of CEO popularity, a short observation period, and its focus on Indonesian listed firms without industry-level analysis. Future research may examine broader sustainability dimensions, explore different institutional contexts, or use qualitative approaches to better understand CEOs’ perceptions of their public image in relation to environmental responsibility.Practical implications – This implies that companies can leverage CEO reputation to improve CCD and meet stakeholder expectations, while regulators may consider promoting disclosure practices that utilize executive visibility as a driver of corporate sustainability.Originality/value – This study addresses a relatively underexplored area by examining the impact of CEO popularity, as manifested through CELEB and STAR status, on CCD in Indonesia. This study makes a pioneering contribution to the literature on corporate sustainability by examining executive reputation as a driver of CCD in emerging markets.